2020
DOI: 10.29309/tpmj/2020.27.09.4586
|View full text |Cite
|
Sign up to set email alerts
|

Study of the characteristics and burden of pediatric trauma in low resource settings.

Abstract: Objectives: Purpose of the study is to identify the characteristics and burden of pediatric trauma in a hospital with limited resources and to compare the results with published literature and to formulate the effective injury prevention strategies. Study Design: Prospective, Descriptive, Cross-sectional study. Setting: Department of Pediatric Surgery, DHQ Teaching Hospital Sahiwal. Period: January 2019 to December 2019. Material & Methods:  A total of 871 patients aged 12 years and below with a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…A study revealed that 14.4% of all deaths in individuals aged 15 and older were due to external causes, with RTIs accounting for almost one-third of these (6,7). A 29% of unintentional injury deaths were attributed to RTIs in 2005, with 8085 road traffic accidents and 1622 fatalities recorded in 2015 alone (8,9). In the United States, trauma is a leading cause of death, particularly in the age group of 1 to 44 years, and is responsible for 20% of all deaths (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that 14.4% of all deaths in individuals aged 15 and older were due to external causes, with RTIs accounting for almost one-third of these (6,7). A 29% of unintentional injury deaths were attributed to RTIs in 2005, with 8085 road traffic accidents and 1622 fatalities recorded in 2015 alone (8,9). In the United States, trauma is a leading cause of death, particularly in the age group of 1 to 44 years, and is responsible for 20% of all deaths (10,11).…”
Section: Introductionmentioning
confidence: 99%